New York Meeting, February 17-20, 1919 (68ff0abe-8191-454a-b1e3-696a3a2afcd0) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1918)
In preparation for the 119th meeting, New York, Feb. 17 to 20, 1919, the following committees have been appointed: Committee on Arrangements ALLEN H. ROGERS Chairman. NY. S. DICKSON, Secretary. J. E. JOHNSON, JR. F. T. RUBIDGE. P. G. SPILSBURY. H. C. PARMELEE. FOREST RUTHERFORD. Committee on Annual Dinner Committee on Luncheon F. T. RUBIDGE. FOREST RUTHERFORD, Chairman. E. B. STURGIS. E. MALTBY SHIPP Committee on Patriotic Meeting H. C. PARMELEE, Chairman.